Tropical design principles for comfortable indoor climate - Dilshan, Remaz Ossen; Abdul Majid, Roshida; Ahmad, Mohd. Hamdan (Faculty of Built Environment, 2008)
It is a generally held view that, in tropical countries, traditional house is more sympathetic to the prevailing climate and provide comfortable interiors. This study analyses the above hypothesis for Tropical House in ‘Taman Tropika’ (TTH) Universiti Teknologi Malaysia (UTM), which was designed emplacing tropical design strategies. This house initiated good ventilation, which indicated indoor temperature similar with the outdoor condition. However, the architectural design solutions do not permit good passive cooling for thermal comfort for whole day. It is illustrated by the indoor temperature above the neutral temperature experienced during the day time. In this research, new tropical building principle has been suggested by adopting Taman Tropika house elements as alternative techniques for achieving passive cooling. The thermal comfort study in this research involved the use of field measurement and computer simulation using ECOTECT software. Validation of ECOTECT is done by comparing the computer simulation result with the field measurement. The results of the new tropical building principles illustrated that the indoor air temperature reduced by 3.5 oC and below the neutral temperature for comfort. The other important factor is that it can continuously maintain the comfortable condition during full day regardless of the available outside climate condition. This effect is significant toward improving the comfortable indoor environment of the tropical house.